2013
DOI: 10.1007/s00894-013-2001-y
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase acidities of N-substituted amine-boranes

Abstract: Complexation energies and acidities of 19 primary, secondary and tertiary amine-boranes were investigated using MP2/6-311+G(d,p) and B3LYP/6-311+G(d,p) methods. Gas phase acidities for free amines were also calculated. Acidity values for studied complexes range from 327.3 to 349.1 kcal mol(-1) and the most acidic are the ones with direct connection between deprotonation center and a π-system. Results obtained by both computational methods are in good agreement with each other and with known experimental data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The calculations were carried out using the GAUSSIAN 09 program package under the programs default conditions (298.15 K and 1 atm) if not stated otherwise. In our work we used MP2 method with 6‐311 + G(d,p) basis set which has been shown to be adequate and relatively cheap method for calculating proton transfer reactions . In some cases, G2 method was also used to calculate energies for different deprotonation centers with close energies.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations were carried out using the GAUSSIAN 09 program package under the programs default conditions (298.15 K and 1 atm) if not stated otherwise. In our work we used MP2 method with 6‐311 + G(d,p) basis set which has been shown to be adequate and relatively cheap method for calculating proton transfer reactions . In some cases, G2 method was also used to calculate energies for different deprotonation centers with close energies.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In our work we used MP2 [18][19][20][21][22] method with 6-311 + G(d,p) basis set [23][24][25][26] which has been shown to be adequate and relatively cheap method for calculating proton transfer reactions. [27][28][29] In some cases, G2 method [30] was also used to calculate energies for different deprotonation centers with close energies. A full conformational search was done for each species and vibrational analyses for zero-point energies, and thermal corrections were performed.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Both values are also comparable to complexation values of amine‐boranes. For example ΔG for unsubstituted amine‐borane is −14.1 kcal/mol and values for substituted complexes vary from −15 to −22 kcal/mol, if we leave aside phenyl substituted amine‐borane with an exceptionally low stability …”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen release reaction as well as intrinsic properties related to hydrogen storage, like gas‐phase basicity and acidity, has been studied . It has been found that complexation greatly alters the properties of amines, for example the acidity is enhanced by 30–50 kcal/mol . The protonation centre of such complexes is located on the boron moiety, and the resulting structure can be described as R 1 R 2 R 3 N‐BH 2 + ••H 2 .…”
Section: Introductionmentioning
confidence: 99%